2017
DOI: 10.15317/scitech.2017.77
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Alternatives for Micropollutant Removal in Wastewater

Abstract: Present of micropollutants in aquatic environments has become an alarming environmental problem for both living creatures and environment. Micropollutants, also called as emerging contaminants arise from natural substances and increasing variety of anthropogenic events. Micropollutants consist of pharmaceuticals, personal care products, steroid hormones, industrial chemicals, pesticides, polyaromatic hydrocarbons and other recently seen compounds. These emerging contaminants are commonly found in very low conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The elimination of pesticides was not significantly influenced by the coagulant dose or the operating temperature. 25 Despite the modest variations among several types of coagulants at various doses, Fenyvesi et al found that the addition of 25 mg/L FeCl 3 generally produced excellent outcomes. Other than dose, a number of operating parameters, such as mixing conditions, pH, alkalinity, temperature, the presence of divalent cations, and concentrations of destabilizing anions, can affect how well coagulation-flocculation processes function.…”
Section: Resultsmentioning
confidence: 99%
“…The elimination of pesticides was not significantly influenced by the coagulant dose or the operating temperature. 25 Despite the modest variations among several types of coagulants at various doses, Fenyvesi et al found that the addition of 25 mg/L FeCl 3 generally produced excellent outcomes. Other than dose, a number of operating parameters, such as mixing conditions, pH, alkalinity, temperature, the presence of divalent cations, and concentrations of destabilizing anions, can affect how well coagulation-flocculation processes function.…”
Section: Resultsmentioning
confidence: 99%
“…Micropollutants are found at microlevels in waste water from health organizations and hospitals, in addition to domestic waste water. They are accepted by the EPA as new xenobiotic chemicals threatening human and environmental health at serious dimensions with all aspects currently unknown (Schwarzenbach et al, 2006;Leminh et al, 2010;Yaşar et al, 2013;Burke et al, 2014;Gulde et al, 2016;Nas et al, 2017).…”
Section: Micropollutantsmentioning
confidence: 99%
“…Não existe um tratamento específico para remover completamente produtos farmacêuticos do efluente, principalmente devido às propriedades distintas de cada um deles (Nas et al, 2017). Assim diversas tecnologias avançadas de tratamento vêm sendo propostas e avaliadas, principalmente em países onde as ações em relação ao controle de micropoluentes está mais evoluída, como Alemanha e Suíça.…”
Section: Introductionunclassified